Centring Indigenous knowledge systems to re‐imagine conservation translocations. Issue 3 (3rd August 2020) - Rayne, Aisling; Byrnes, Greg; Collier‐Robinson, Levi; Hollows, John; McIntosh, Angus; Ramsden, Mananui; Rupene, Makarini; Tamati‐Elliffe, Paulette; Thoms, Channell; Steeves, Tammy E.
Abstract: Conservation translocations—particularly those that weave diverse ways of knowing and seeing the world—promise to enhance species recovery and build ecosystem resilience. Yet, few studies to date have been led or co‐led by Indigenous peoples; or consider how centring Indigenous knowledge systems can lead to betterconservation translocation outcomes. In this Perspective, as Indigenous and non‐Indigenous researchers and practitioners working in partnership in Aotearoa New Zealand, we present a novel framework for co‐designing conservation translocations that centre Indigenous peoples and knowledge systems through Two‐Eyed Seeing. We apply this framework to Aotearoa New Zealand's threatened and underprioritized freshwater biodiversity. In particular, we highlight the co‐development of conservation translocations with Te Kōhaka o Tūhaitara and Te Nohoaka o Tukiauau that are weaving emerging genomic approaches into mātauraka Māori (Māori knowledge systems), including customary practices, processes and language. We envision the Two‐Eyed Seeing framework presented here will provide a critical point of reference for the co‐development of conservation translocations led or co‐led by Indigenous peoples elsewhere in the world to build more resilient biocultural heritage. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article Auheke: Torutoru noa iho kā nekeneke o kā momo tata korehāhā kua puta mai i te mahi tahi a kā iwi taketake me kā kairakahau. Tēnā pea mā te mātauraka o kā iwi taketake, ka whakahaumako i te whāomoomo o te pūnaha hauropi. Kua hakaia he pou tarāwaho e mātou hei whakakaupapa i kā mahere neke momo tata korehāhā. Ko te kako o tēnei pou tarāwaho ko te arotahika ki kā mātauraka o kā iwi taketake kia āwhina i ēnei mahi. Mai i te whakakotahitaka o kā rarauka huika ira me kā momo mātauraka Māori—mai i kā mahika kai, tae ana ki te reo—ka whakatinana mātou i tēnei pou tarāwaho ki kā momo tata korehāhā i kā wai o Te Kōhaka o Tūhaitara me Te Nohoaka o Tukiauau. Ko te tūmanako ka whakatinana tēnei pou tarāwaho e kā iwi taketake me kā kairakahau o te ao whānui ki te hāpai i te whāomoomo o kā koiora mai i ō rātou whenua.